LongITools: Dynamic longitudinal exposome trajectories in cardiovascular and metabolic noncommunicable diseases. Issue 1 (28th February 2022) - Ronkainen, Justiina; Nedelec, Rozenn; Atehortua, Angelica; Balkhiyarova, Zhanna; Cascarano, Anna; Ngoc Dang, Vien; Elhakeem, Ahmed; van Enckevort, Esther; Goncalves Soares, Ana; Haakma, Sido; Halonen, Miia; Heil, Katharina F.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : The current epidemics of cardiovascular and metabolic noncommunicable diseases have emerged alongside dramatic modifications in lifestyle and living environments. These correspond to changes in our "modern" postwar societies globally characterized by rural-to-urban migration, modernization of agricultural practices, and transportation, climate change, and aging. Evidence suggests that these changes are related to each other, although the social and biological mechanisms as well as their interactions have yet to be uncovered. LongITools, as one of the 9 projects included in the European Human Exposome Network, will tackle this environmental health equation linking multidimensional environmental exposures to the occurrence of cardiovascular and metabolic noncommunicable diseases.